Relationship Between Enablers and Barriers to Financial Inclusion—the Case of North Macedonia - Eftimovska, Natasha (International Finance and Banking, 2024)
This research aims to examine the relationship between factors that act as enablers or barriers to financial inclusion, as independent variables, and the environment for financial inclusion, as a dependent variable, for the case of North Macedonia. For accomplishing the main research objective, first, the factors that act as enablers or barriers to financial inclusion were identified by collecting primary data using questionnaires and performing comparative analysis on our country’s position with different regions categorized by income groups and World, through the benchmarking model of Global Microscope (Economist Intelligence Unit, 2018. Global Microscope 2018. The Enabling Environment for Financial Inclusion. The EIU, The Economist). Second, primary data from questionnaires served to furtherly examine the correlation between each identified enabler or barrier to financial inclusion and the overall environment for financial inclusion through multiple regression analysis. Results revealed important information and recommendations for the future focus of national priorities, institutional arrangements, policies, and strategies in terms of creating enabling environment for financial inclusion, benefits of which can be felt by the overall society.